Ars musica w krakowskich traktatach muzycznych XVI wieku - Witkowska-Zaremba, Elżbieta 1946- (Kraków PWM, 1986)
The Cracow Plainsong Treatises of the first half of the 16th century represent a virtually unknown though very important part of Polish musical literature in the period. They are the only texts of their time which, in addition to their precepts on the practice of music, also provide answers to such basic questions as: What is music? What makes a musician? What is the subject of the study of music? What is the derivation and what is the purpose of music? The answers to these questions formulated in the plainsong treatises established some of the foundations of musical knowledge about music and went some way towards shaping a common view of its nature and function. (...)
Summary in English
Keywords: 16th Century (1501-1600); 20th Century (1901-2000); Music theory; Plainchant; Music history; Method; Kraków (Poland)